Effects of α-enolase gene silencing on reproductive-related hormone receptor expression and steroid hormone synthesis of primary granulosa cells from goose F1 follicles - Ji Hong (Sciendo, 2020)
Enolases are enzymes in the glycolytic pathway, which catalyse the reversible conversion of D-2-phosphoglycerate into phosphoenol pyruvate in the second half of the pathway. In this research, the effects of α-enolase (ENO1) on steroid reproductive-related hormone receptor expression and on hormone synthesis of primary granulosa cells from goose F1 follicles were studied.